PENGARUH USAHATANI GULA KELAPA TERHADAP TINGKAT KESEJAHTERAAN PENGRAJIN GULA KELAPA DI KECAMATAN CIKALONG KABUPATEN TASIKMALAYA - Nurhasanah, Hanna (2014)
KecamatanCikalongKabupatenTasikmalayamerupakanlokasi yang produktifuntuktanamankelapadanmasyarakatnyamemanfaatkantanamantersebutmenjadimatapencaharianpokokberbasisusahataniyaitusebagaipengrajingulakelapa.Usahatanigulakelapasebagaimatapencaharianpokokseharusnyamemberikankontribusiterhadappendapatandantentunyamenentukantingkatkesejahteraanpengrajin.Pengrajingulakelapa di KecamatanCikalong rata-rata tidakmemilikilahansendiri, danalatpengolahangulakelapamasihtradisional.Selainitujugapengrajinhanyamelibatkantengkulakdalammemasarkangulakelapayang menyebabkanhargajualnyalebihrendah, sehinggabiladilihatdaritingkatkesejahteraanpengrajinnampaknyabelumbaik.Olehkarenaitu, tujuandaripenelitianiniyaituuntukmengidentifikasiproduksigulakelapadantingkatkesejahteraanpengrajinsertamenganalisispengaruhusahataniterhadaptingkatkesejahteraan.Metode yang digunakandalampenelitianiniadalahmetodedeskriptif.Populasipenelitianinimeliputiseluruhpengrajingulakelapadi KecamatanCikalongberjumlah 3.030 dansampel 80 responden yang berada di DesaTonjongsari, DesaCikancradanDesaCikalong.Pengambilan data menggunakanteknikobservasi, angketdanwawancara.Data yang terkumpuldianalisismenggunakananalisispersentase, analisis crosstab dananalisiskorelasiSpearman Rank.Variabelpenelitianmeliputivariabelbebasyaitufaktor-faktorproduksiusahatanigulakelapadiantaranya Input (lahan, bahanbaku, tenagakerja, dan modal), Proses (Alat, pengolahangulakelapa, danenergy) serta Output (Kuantitas, kontinuitas, kualitas, hargadanpemasaran) sertavariabelterikatyaitutingkatkesejahteraanmenggunakan 23 indikatormenurutBKKBN. Hasilpenelitianmenunjukkanbahwahubunganproduksigulakelapadengantingkatkesejahteraanmenunjukkannilaikoefisienkorelasi -0.082 dengannilaiSig 0,468 lebihbesardari 0,05 artinyakeduavariabeltidakadapengaruhdantidaksignifikan. Sedangkanhubunganpendapatandengantingkatkesejahteraanmenunjukkannilai0,035 yang artinyaadahubungannamunsangatkecilataulemahdannilaiSig 0,757 lebihbesardari 0,05 artinyakeduavariabeltersebuttidaksignifikan.Hal inidikarenakanindikatortingkatkesejahteraan BKKBN mengukurpadakondisipangan, sandang, papan, sosial, agama, kesehatan, psikologisdanpengembangannya. Cikalong district of Tasikmalaya regency is a productive location which is suitable for coconut plantation. People in Cikalong use coconut as raw material for making palm sugar. But from that comes a problem, the producers' do not their own coconut plantation to provide raw material . They have to lease coconut trees. They still also use modest production tool in order to process the raw material. In term of marketing, they do not have capability to distribute their product on their own. They still rely on brokers to sell the product. The aim of this research is to identify the palm sugar production, welfare level, and the influence of palm sugar business on their welfare. Descriptive method was employed in this research. There are two variables in this research, first one is independent variable which are palm sugar production factor that includes land, raw material, labor force and funding, the next one is processing that includes production tools, sugar processing, energy, an time that is needed for processing, and another part of independent variable is output that includes quality, quantity, continuity, price and marketing. The second variable is dependent variable that according to Sajogyo is based on 23 indicators which include three basic needs (clothing, food, and homestay), social, religion healthiness, psychology and furthermore includes poverty level. The population in this research were 3030 palm sugar producers and the sample were 80 respondents from Tonjongsari, Cikancra, and Cikalong village. This research were using observation, questioners, and interview in order to collect the data. The collected data were then shortened and analyzed by using percentage analysis, crosstab analysis to correlate the variables and correlation production moment analysis to calculate the correlation coefficient. The result shows that palm sugar business is the main job which contribute greatly to the income of producers. The data analysis shows a correlation between a palm sugar production and welfare level showed a correlation coefficient -0.082 andSig value0,468 which means it does not have correlation. correlatioan between income and welfare level shows the value of0,035that means there are a correlationandSig value 0,757 bigger than 0,05 that is meannot significant.The correlation results because of the BKKBN welfare indicators include the condition of food, clothing, housing, social, religious, health, and psychological furthermore.